Challenge of edible oils: Can Brassicas deliver (Journal of Oilseed Brassica, 2026)
Agriculture University, Ludhiana, Dr. P.R. Verma, Agriculture and Agri-Food Canada, Research Station, Saskatoon, Canada, Dr. S.J. Kolte, Ex Professor, GB Pant University of Agriculture and Technology, Pantnagar, Professor Martin Barbetti, University of Western Australia, Deans, Directors of State Agricultural Universities (SAUs), Directors of ICAR Institutes, representatives from private sector, distinguished participants, media personnel, ladies and gentlemen.